Searching for Plastic Expressiveness in Alexander Osmerkin’s Paintings: From "Cezannism" to "Silent Realism" - Kirichenko, Elena; Punhina, Olha; Malezhyk, Yuliia (Journal of History Culture and Art Research, 2020)
The article discusses the specifics of understanding the plastic expressiveness of painting by A. Osmerkin, which manifested itself differently at different stages of the artist’s creative biography, determined by the sociocultural context of the 1920s – 1940s. The study revealed the aesthetic positions of the artist at an early and mature stage of creativity, reflecting priorities in the search for the plastic expressiveness of the painting. The figurative and stylistic features of his works created in different decades are considered; a comprehensive analysis of his aesthetic views and their reflection in the author’s picture of the world has been performed. In addition, the authors introduce into the scientific circulation the artist’s works from the museums of the Kropyvnytsky city, which were not previously considered in existing publications on the work of A. Osmerkin. The results of the study led to the conclusion that the artist paid great attention to the plasticity of color, with the help of which he built form and space, without taking the color composition from the task of the image. It was not the colorfulness itself that attracted spectators to the artist’s paintings, but precisely the harmoniously constructed color that conveys the beauty of nature in its individual state through the color ratio. In the post-revolutionary time, A. Osmerkin became a consistent realist, working in chamber genres, he was interested not so much in the plot as in solving plastic problems by means of impressionistic painting. At this stage, the artist strives for pictures in the most "nonpainting" genres – in still life, landscape, portrait, working in a peculiar style of "quiet realism". Lyristic imagery of Osmerkin’s paintings puts him among the artists who poetically reflect the world.